EU’s Innovative “Missions” and Convergence Tools to ensure the “Twin Transition” towards Smart Cities and Communities - Cristina Patrascu (Bulletin of the Transilvania University of Braşov: Series VII: Social Sciences, Law)
The present article proposes an analysis of the convergence tools in the domain of the „twin transition”, namely the digital and green (ecological) transition, considered vital in ensuring a sustainable development and a better life for citizens across the European Union. The focus will be placed on the main legislative instruments created by EU’s institutions to secure a coordinated and uniform implementation of the UN’s sustainable development goals, as well as EU’s commitment to create climate-neutral and smart cities and communities.